Hubungan Internet Parenting terhadap Perilaku Cybersex pada Remaja - Nadia Lavia; Maya Yasmin (Jurnal Medika Nusantara, 2024)
This study aims to look at the relationship between internet parenting and cybersex behavior in adolescents. This study used a correlational quantitative approach involving 270 adolescents with an age range of 15-19 years selected through snowball sampling technique. Data analysis using product-moment correlation analysis which produces a correlation coefficient hypothesis of -0.211, p=0.000 (p < 0.05) indicates that there is a negative relationship between internet parenting and cybersex behavior in adolescents, where the higher the internet parenting, the lower the cybersex in adolescents, and the lower the internet parenting, the higher the cybersex in adolescents. One way that can be done to reduce cybersex behavior is to increase internet parenting towards internet use in adolescents.